CORROSION INHIBITION OF CARBON STEEL IN HYDROCHLORIC ACID (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
The corrosion of carbon steel in 0.3 and 3% mass hydrochloric acid containing the concentration range 50-800 ppm of Thiourea (Th), Quinoline (Q), Dliethylamine (DEA) and Pyridine (P) were investigated using electrochemical methods. The investigation aims to mention the best organic inhibitor among several compounds to be used in synergic inhibitors. The inhibition efficiencies of thiourea and quinoline are better than pyridine and diethylamine in 0.3 mass% HCl. Thiourea is better than quinoline in 3 mass% HCl and its inhibition efficiency is 83.7%. Generally, the corrosion rate decreases with increasing inhibitors concentration. Diethylamine and pyridine are not effective. The polarization curves indicate that the used inhibitors influenced the cathodic reaction more than the anodic reaction and they are considered as a mixed type inhibitors